Do Rural–Urban Differences in Social Environments Act as Barriers to Social Wellbeing? A Cross-Sectional Study - Kiffer Card; Jorge Andrés Delgado-Ron (Urban Science, 2025)
Loneliness and social isolation are pressing public health concerns, prompting interest in how rural and urban environments shape social wellbeing. However, evidence remains mixed—perhaps because loneliness is a distal psychological outcome with complex, trait-like stability. To address this, we examined geographic variation in upstream patterns of social activity using data from the 2023 Canadian Social Connection Survey (N = 1556). The principal component analysis identified five domains of social behavior, which we analyzed using multivariable regression and supplemented with a series of sensitivity and stratified analyses. Our findings suggest that while broad differences across rural and urban geographies are modest, specific domains of behavior show some variation. For example, residents in rural areas reported lower casual social interaction (b = −0.19, p = 0.019) but similar or even greater engagement in intimate and supportive behaviors. Emotional loneliness was slightly lower in small towns (b = −0.17, p = 0.029), indicating possible protective effects of some smaller community contexts. While the overall structure of social behavior was not invariant across settings, general patterns of engagement appeared largely resilient to geographic differences. These findings underscore the importance of place-sensitive strategies that respond to specific forms of social behavior affected by geography while avoiding overgeneralized assumptions about rural–urban disparities.